(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
The study of the profile of graduates from postgraduate courses helps to (re) formulate the strategic planning of postgraduate programs while contributing to public policies, institutional or social practices. In this sense, objectively characterize the profile of graduates of the Postgraduate Program in Information Science at the Federal University of Alagoas, considering the period from 2021 to 2023. The methodology is presented as descriptive, regarding the procedures, it is classified as documentary and bibliographic and its approach is the quantitative method. Through three categories: identification; training and occupation; and scientific production, it was possible to obtain as a result the prevalence of women in the Program, the need for postgraduate studies to be more integrated into the job market and an increasing scientific production on the part of graduates.